Copyright Protection of Art Containing Nudist Elements Under Positive Law In Indonesia - Mohamad Nur Kholiq; Dinda Ajeng Puspanita; Prawitra Thalib (Law and Justice, 2021)
In Law No. 28 of 2014 concerning Copyright, copyright can be granted to photography and painting as works of art produced by human creativity and initiative. Problems arise in realism works of art in the form of painting or photography containing nudist elements. By applying normative juridical research approaches of legislation (statute approach) and conceptual approach, this study examined restrictions based on the meaning of one article that works being the object of copyright protection must comply with morals, religion, morality, public order or national defense and security. The findings revealed that copyright objects in the form of works of art containing nudist elements, as long as they follow the culture of the local community and are not intended to arouse sexual arousal, are entitled to copyright protection.